Preliminary study on nitrate injection to control souring problem in oil reservoir: Benefits and side effects on steel material (UNS S31603) - Halim, A.; Gubner, Rolf (2011)
Nitrate injection is a common approach used to control reservoir souring. This method relies on nitrate reducing bacteria (NRB) ability to suppress sulphate reducing bacteria (SRB) growth. These experiments were conducted to investigate the underlying principal of nitrate injection to stainless steel material. Anaerobic tests were performed by immersing UNS S31603 samples for 28 days at 50°C in electrochemical cells containing 10% crude oil in brine water, supplemented with sodium nitrate. Four different conditions were evaluated: control cell (no bacteria), NRB inoculated cell, SRB inoculated cell and Mixed (NRB and SRB) bacteria inoculated cell. The Open Circuit Potential (OCP) of the steel was monitored throughout the test. In addition, Linear Polarization Resistant (LPR) and Cyclic Polarization Scan (CPS) were carried out at the end of the immersion time. These results demonstrated that the addition of nitrate promoted NRB growth and suppressed SRB growth; hence H2S production can be eliminated. However, NRB formed patchy biofilms on the steel surfaces that weakened steel passivity and decreased its Critical Pitting Potential (CPP). This makes the steel more susceptible to localized corrosion.